2017
DOI: 10.3389/fneur.2017.00599
|View full text |Cite
|
Sign up to set email alerts
|

Current Opportunities for Clinical Monitoring of Axonal Pathology in Traumatic Brain Injury

Abstract: Traumatic brain injury (TBI) is a multidimensional and highly complex disease commonly resulting in widespread injury to axons, due to rapid inertial acceleration/deceleration forces transmitted to the brain during impact. Axonal injury leads to brain network dysfunction, significantly contributing to cognitive and functional impairments frequently observed in TBI survivors. Diffuse axonal injury (DAI) is a clinical entity suggested by impaired level of consciousness and coma on clinical examination and charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 231 publications
(280 reference statements)
0
21
0
Order By: Relevance
“…Increased GFAP, NFL, and MBP CSF level in head injury patients corresponded with frontal lobe disseminated astrocyte clasmatodendrosis, neurofilament rupture, and diminished MBP expression, respectively. Astrocyte clasmatodendrosis and neurofilament rupture may be related to primary and secondary axotomy -due to oedema, raised intracranial pressure, cerebral blood flow dysfunction (ischemia and hypoxia), and as well changes at the cellular level, such as glutamate excitotoxicity, ionic imbalance, dysfunction of mitochondria, oxidative stress, inflammatory factors release, necrosis and apoptosis [13,29]. We find the diminished MBP expression which could be a result of secondary processes including intracellular calcium overload from glutamate toxicity or mitochondrial dysfunction and oxidative stress [2,26].…”
Section: Discussionmentioning
confidence: 99%
“…Increased GFAP, NFL, and MBP CSF level in head injury patients corresponded with frontal lobe disseminated astrocyte clasmatodendrosis, neurofilament rupture, and diminished MBP expression, respectively. Astrocyte clasmatodendrosis and neurofilament rupture may be related to primary and secondary axotomy -due to oedema, raised intracranial pressure, cerebral blood flow dysfunction (ischemia and hypoxia), and as well changes at the cellular level, such as glutamate excitotoxicity, ionic imbalance, dysfunction of mitochondria, oxidative stress, inflammatory factors release, necrosis and apoptosis [13,29]. We find the diminished MBP expression which could be a result of secondary processes including intracellular calcium overload from glutamate toxicity or mitochondrial dysfunction and oxidative stress [2,26].…”
Section: Discussionmentioning
confidence: 99%
“…Axon pathology induced by TBI has been well recognized in the field of TBI research. Diffuse axonal injury is a direct consequence of mechanical injury and induces neurodegeneration and functional deficits [61,62]. In our present long-term TBI study, the axonal injury marker, APP, is not detectable in the brain 24 weeks after TBI, suggesting that the fast axonal transport accumulation of APP may occur only in the acute phase, but not in the late subacute phase of TBI.…”
Section: Discussionmentioning
confidence: 49%
“…Axon pathology induced by TBI has been well recognized in the field of TBI research. Diffuse axonal injury is a direct consequence of mechanical injury and induces neurodegeneration and functional deficits [57,58]. However, few, if any, research reported the overgrowth of axons after TBI.…”
Section: Discussionmentioning
confidence: 99%